Information security and cryptology : 10th International Conference, Inscrypt 2014, Beijing, China, December 13-15, 2014, Revised selected papers /: 10th International Conference, Inscrypt 2014, Beijing, China, December 13-15, 2014, Revised selected papers. (2015) - Unknown
No abstract available